Evaluation of facilities for science of teaching in grade V and VI in the Division of Rizal - Magno, Martha G. 1928- (College of Education, University of the Philippines Diliman, 1966)
This study investigated the provisions in terms of facilities that should be made available for an effective elementary science program in the opinion of science education specialists, the science facilities for grades V and VI that are actually present in 36 public elementary schools in Rizal and their adequacy as teaching facilities.